Invivo Impact of Malaria and HIV Co-Infection on CD4 Cell Count of Infected Patients of Niger Delta Extraction - Azuonwu Obioma; Ihua Nnnena; Nwaokorobia Judith (Journal of Advanced Pharmaceutical Science And Technology, 2020)
The study evaluated the impact of co-infection of malaria parasitaemia, and HIV positive indices on the CD4 cell count of 120 HIV infected subjects, who were already diagnosed and visiting Braithwaite Memorial Specialist Hospital Port Harcourt for routine Medical check-up. Also, a control group of 40 HIV negative were included as part of the study control group. The subjects were between the age ranges of ≤10–79 years respectively. A double check laboratory assay was conducted to detect the presence of antibody to HIV as confirmed using immunocomb 11 and Determine for HIV status. A thick Blood film stained with field stain (A and B) was used to detect the presence of malaria parasite in the subject’s blood. Furthermore, CD4 cell count was assayed using Partec cyflow counter (Partec, Germany). Excel and Graphpad statistical software were used for analysis of the data generated. The result among the HIV positive subjects and control subjects revealed that the highest positive for malaria infection was observed among ≤10 years age group as 2 (100%) and 11 (84.61%) respectively. In the HIV positive subjects, the distribution of malaria infection among sex revealed a high rate in male 42(77.78%) than in female 44 (66.67%). Similarly, the control recorded a high rate of malaria infection in male 11 (57.89%) than in female 7 (33.33%). However, 86 (71.67%) had malaria and HIV co-infection while 34 (65%) had only HIV mono infection. The positive HIV subjects who had CD4 cells count below 200 cells/mm3 were 15%, above 200-499cells/mm3 were 58.3% while 500 cells/mm3 and above had normal CD4 cells counts for 26%. Nonetheless, for the control subjects, no CD4 cells count of below 200cells/ mm was observed, 2.5% fell within the moderate category while 75% had normal CD4 cells count. Statistical analysis using ANOVA and t-test showed that there is significant difference between CD4 of seropositive and seronegative subjects infected with or without malaria (p=0.00). In addition, a t-test further demonstrated Comparison of Mean CD4 Cell Count among HIV and Malaria Infected and Non-Infected Subjects. MP/HIV Co-Infection and Mono Infection with No Infection showed strong mean difference (p=0.00) in the various CD4 counts while HIV Mono-Infection and others only had a non significant (p=0.44) mean difference between HIV Mono-Infection and No HIV or Malaria Infection. A robust and effective malaria and HIV control management programme should be strongly underpinned; so as to improve the quality of life of patients and HIV patients should be encouraged to live a healthy life style, through the provision of antiretroviral drugs and regular health education engagement, even as the provision of antimalarial treated net would be helpful to the subjects.
Keywords: Impact